Professional training of state employees - an important element of civil service - Гончарук, Степан Тихонович; Олійник, Ірина Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article examines issues related to clarifying the legal status of civil servant, his rights and obligations, demands it, the civil service and above all administrative and legal regulation of training civil servants under the new legislation of Ukraine. Attention is drawn to the fact that the need for continuing professional competence of a public servant is one of the main duties of his professional career. This often focuses in the new law on public service. In particular, this principle of public service as professionalism provides competent, objective and impartial performance of official duties, the constant improvement of civil servant of his professional competence. Permanent enhance their professional competence attributed to the fundamental rights and duties of a public servant. Managers of public service in government agencies, service personnel management required to ensure the possibility of passing civil servant vocational training required civil servants to perform their duties, to create conditions to improve his skills and level of professional competence. Requirements for persons applying for admission to the civil service are the requirements for their professional competence. Professional competence of the civil servant law as determined by the ability of individuals within certain officio powers to apply specific knowledge and skills, identify appropriate moral and professional qualities to properly perform assigned tasks and responsibilities, training, professional and personal development. General Procedure for improving the professional competence of civil servants defined by law on public service (Art. 48) and the Regulations on the system of training, retraining, specialization and training of civil servants approved by the Cabinet of Ministers of Ukraine dated July 7, 2010 as amended on September 27, 2016 g.